Carbonylation of tertiary carbon radicals: synthesis of lactams. Issue 32 (1st April 2019) - Yin, Zhiping; Zhang, Zhuan; Zhang, Youcan; Dixneuf, Pierre H.; Wu, Xiao-Feng
Abstract : Herein, we disclose an interesting iron-catalyzed approach for the carbonylation of a tertiary carbon radical. Abstract : Herein, we disclose an interesting iron-catalyzed approach for the carbonylation of a tertiary carbon radical. The tertiary carbon radical generated from a 1, 5-hydrogen atom transfer can be captured by CO gas smoothly. Various six-membered lactams were constructed chemo-selectively in high yields.